Adherence of Patients with Chronic Renal Failure to Therapeutic Regimen (Cuestiones de Fisioterapia, 2024)
Background: Chronic renal failure is a global health and healthcare burden that is rapidly increasing. Therapeutic adherence is a crucial factor that helps these patients to achieve good therapeutic results and reduces morbidity and mortality. Adherence to the treatment was affected by several factors which are grouped to treatment regimen, psychosocial and economic factors, the factors related to healthcaresystem and the factors related to illness